JUSTICE OR EQUALITY? EXAMINING ARTICLE 97 OF THE KHI IN THE CONTEXT OF POST-DIVORCE PROPERTY DIVISION - Maya Anggraeni Rahmah Permana; Abdul Rachmad Budiono; Hanif Nur Widhiyanti (CV. RADJA PUBLIKA, 2025)
This study aims to critically analyze the provisions of Article 97 of the Compilation of Islamic Law (KHI) in the context of the division of joint assets after divorce, emphasizing the need for legal reform that prioritizes the principle of substantive justice. The main issues examined include the extent to which these provisions reflect the principle of substantive justice and how Article 97 of the KHI is implemented in religious court practice. The research method used is normative juridical with a statutory, conceptual, and case-based approach. The results show that Article 97 of the KHI is still oriented towards rigid arithmetic equality and does not consider the actual contributions, both material and immaterial, of each party. In judicial practice, a number of judges have implemented progressive interpretations of this norm, which opens up space for the reformulation of Islamic family law in Indonesia. Therefore, this study recommends normative reform of Article 97 of the KHI to include provisions that explicitly accommodate proportional division of assets, as well as implementing steps in the form of training on a substantive justice perspective for judges.